Shame and the body in Psalms and Lamentations of the Hebrew Bible and in Thanksgiving Hymns from Qumran - Stiebert, Johanna (Old Testament essays, 2007)
While the songs of the Psalter and Lamentations of the Hebrew Bible share much in common with the Thanksgiving Hymns from Qumran, both in terms of form and content, a careful examination of the concept of shame and its associations with the human body reveals striking differences, including theological differences. Whereas shame and suffering in Lamentations are attended by protest and attempts to rouse divine pity and mercy, in Psalms they are on the one hand endured and on the other alluded to in order to procure similar divine punishments for adversaries. In Thanksgiving Hymns, on the other hand, shamefulness is accepted as sharing the same inevitability as impurity. It is hoped that this article will facilitate more nuanced readings of poetic shame-imagery in both biblical and extra-biblical literature.